Acid-base regulation in rainbow trout: The roles of carbonic anhydrase and cortisol - Collier, Christina Lee (University of Ottawa (Canada), 2007)
This study tests the hypotheses that compensation for metabolic acid-base disturbances involves regulation of carbonic anhydrase (CA) and that cortisol plays an important role in mediating the compensatory responses of the rainbow trout, Oncorhynchus mykiss. Metabolic acidosis decreased mRNA expression of branchial trout cytosolic CA (tCAc) and increased mRNA expression of renal tCAc and membrane-bound CAIV (tCAIV). Metabolic alkalosis increased mRNA expression of branchial and renal tCAc, decreased renal tCAIV mRNA expression, and increased branchial CA activity. Plasma cortisol was elevated during acidosis and alkalosis, indicating its possible involvement in regulating the response to an acid-base challenge. Cortisol may up-regulate CA, as treatment with exogenous cortisol increased tCAc and tCAIV mRNA expression, renal tCAc protein abundance, and branchial CA activity. This study suggests that CA contributes to the compensation of metabolic acid-base disturbances in the rainbow trout, and that cortisol is involved in the regulation of acid-base status.
Keywords: Biology, Animal Physiology.